2017
DOI: 10.22175/mmb2017.05.0028
|View full text |Cite
|
Sign up to set email alerts
|

National Beef Tenderness Survey—2015: Palatability and Shear Force Assessments of Retail and Foodservice Beef

Abstract: Beef retail steaks from establishments across 11 US cities and beef foodservice steaks from establishments in 6 US cities were evaluated using Warner-Bratzler shear (WBS) force and consumer sensory panels. The average postfabrication aging time of steaks at retail establishments was 25.9 d with a range of 6 to 102 d, and those from foodservice establishments averaged 31.5 d with a range of 3 to 91 d. The retail steaks with the lowest WBS value (P < 0.05) was the boneless top loin, compared to the top round ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 12 publications
8
38
4
Order By: Relevance
“…WBS force values were not found to differ (P � 0.5951) among Farmers Market ribeye, top loin, or top sirloin steaks. ese results are in agreement with findings from both the 2010 and 2015 NBTS by Guelker et al [8] and Martinez et al [9]; respectively, who found no significant differences in WBS force values between retail ribeye, top loin, and top sirloin steaks. ese similarities can be attributed, in part, to the muscles that are in each of these three steak cuts.…”
Section: Warner-bratzler Shear Forcesupporting
confidence: 92%
See 4 more Smart Citations
“…WBS force values were not found to differ (P � 0.5951) among Farmers Market ribeye, top loin, or top sirloin steaks. ese results are in agreement with findings from both the 2010 and 2015 NBTS by Guelker et al [8] and Martinez et al [9]; respectively, who found no significant differences in WBS force values between retail ribeye, top loin, and top sirloin steaks. ese similarities can be attributed, in part, to the muscles that are in each of these three steak cuts.…”
Section: Warner-bratzler Shear Forcesupporting
confidence: 92%
“…As the industry continues to cope with increases in carcass size, merchandising techniques and steak thicknesses have fluctuated to achieve desired portions. Martinez et al [9] found boneless top loins were thicker than boneless ribeyes and top sirloins. Voges et al [11] also reported a greater mean steak thickness for ribeye and top loin steaks than top sirloin steaks.…”
Section: Steak Measurementsmentioning
confidence: 96%
See 3 more Smart Citations